Pengemasan Karakter Perempuan di Film Horor Indonesia Terlaris Periode 2017-2022 - Wijayanti, Sri (Jurnal Mahardika Adiwidia, 2023)
Horror films are a commercial and popular genre for Indonesian audiences. Female characters are often the main attraction of Indonesian horror films. In its development there are changes in the portrayal of female characters in Indonesian horror films in the 2000s. For this reason, this study aims to determine the packaging of female characters displayed in the 20 best-selling Indonesian horror films produced in 2017-2022. The research method used qualitative content analysis of the presentation of main and auxiliary female characters with a focus on the film's sub-genre, duration, role and characterization, and female image. The research findings show that females are starting to be represented as progressively formulated characters. This means that females are still used as prominent main characters in the story. However, in different packaging, among others, the role of females is transformed into fighters and protagonists. The characterization of female characters is made more substantive by raising new story standards, supported by an aesthetic cinematographic style. The mecca of content based on family issues, cultural myths, and social themes is a new standard of story quality in Indonesian horror films.